Severe Malaria with Multiple Complications - Andrio Palayukan; Nisan Soeheri (PT Kalbe Farma Tbk., 2024)
Background: Malaria is still a major global health concern with a high mortality rate. The clinical spectrums of malaria range from mild to life-threatening. Case: A 25-year-old male with weakness, fever, and anuria. Physical examination showed febris, jaundice, and abdominal tenderness at the right upper quadrant. Laboratory findings revealed Plasmodium falciparum hyperparasitemia with increased total bilirubin and creatinine levels. Diagnosis of severe falciparum malaria with multiple complications (cholecystitis, acute kidney injury, and anemia) was established. Intravenous antimalarial and antibiotics were administered along with hemodialysis. The patient was discharged after 11 days of treatment with the improvement of clinical status and laboratory parameters. Conclusion: A comprehensive approach to the diagnosis of malaria is necessary to detect complications and appropriate management.